SOURCES OF INSPIRATION, CONTEXTS AND PARALELLS (Mūzikas akadēmijas raksti, 2024)
The overview of Einfelde’s life story confirms that her music was influenced by various factors – childhood memories, concert life impressions, ancient myths and contemporary literature, memories of personalities that had already passed away, tragic events in the second half of the 20th century, among others. To what extent does the interpretation of these motifs manifest the characteristic traits of Einfelde’s musical stylistics? The goal of this article is to look for the answer to this question. To achieve this, three themes are analysed.